The Polish Mayor of Warsaw Julian Kulski and the Holocaust: Administration, Collaboration and Contextualization - Rossoliński-Liebe, Grzegorz (Zeitschrift für Religions- und Geistesgeschichte, 2026)
This article examines how Julian Kulski - the mayor of the largest city in the General Government - acted during the persecution and the murder of the largest urban Jewish community in Europe. Taking into account the ghettoization, anti-Jewish regulations, forced labor, dismissal of Jewish employees, appropriation of property, tax collection and deportations, the article shows that the city administration of the former Polish capital and its mayor were deeply involved in the persecution of Warsaw Jewry and should be included in the history of the Holocaust and German occupation in Poland. Because Kulski came from a family with a Jewish background and helped his wife to hide a few Jews, his administrative collaboration with the Nazis during the German occupation of Poland and the annihilation of Warsaw Jewry suggest that he was a man of contradictions and that we need a complex approach to research the collaboration of Polish civil servants with the Nazis.